Islamic Religious Education Teachers' Efforts to Improve Learning Achievement of Junior High School Students - Sahli, Ahmat (CV. Strata Persada Academia, 2024)
This research aims to describe what efforts have been made to improve student learning achievement at SMPN 1 Grobogan. This research uses a descriptive qualitative approach. The primary data sources in this research are the principal, deputy principal, and Islamic religious education teacher. From the results of the research carried out in this study, PAI teachers' efforts to improve student learning achievement at SMPN 1 Grobogan include, among other things, providing motivation, varied strategies, and methods appropriate to the situation and conditions as well as media that is interesting and appropriate to the material. In the PAI teacher's efforts, there are several obstacles, including students with low abilities, limited supervision, and a lack of student awareness of the importance of learning. The solutions to these obstacles include the school providing exceptional guidance to students with low abilities; there is cooperation between parents and the school to provide supervision and raise students' awareness of the importance of learning.